[OP.3C.04] PREDICTING POSTURAL HYPOTENSION, FALLS, AND COGNITIVE IMPAIRMENT: THE INCHIANTI STUDY. (September 2016) - Clark, C.; Thomas, D.; Warren, F.; Llewellyn, D.; Ferrucci, L.; Campbell, J.
Abstract : Objective: Over three million people aged over 65 fall each year in the UK. Postural hypotension (PH) is a risk factor for falls. It is associated with excess mortality, and may affect cognition. PH is not routinely checked for in UK clinical practice. We studied the InCHIANTI dataset to derive and validate a simple prediction tool designed to facilitate identification of subjects to be checked for PH. Design and method: InCHIANTI is a population-based study of ageing. It recruited subjects from population registries in Chianti, Italy in 1998 and they were followed up triennially. Blood pressure (BP) at recruitment was measured after resting supine, and one and three minutes after standing, using a mercury sphygmomanometer. Systolic PH was defined as a > = 20 mmHg fall in supine BP on standing. Subjects were randomised to derivation or validation cohorts; allocation was undertaken blinded to PH status and medical history. Candidate predictor variables identified from literature searches were tested for univariable cross sectional associations with PH using χ2 tests. Those with significant associations were entered into multivariable linear regression models, and used to derive simple and weighted prediction scores (DROP scores). DROP scores were tested in the validation cohort for prediction of PH, future falls, cognitive decline and mortality rates. Results: PH was present in 56/726 (7.7%) of the derivation cohort and 45/727 (6.2%) of the validation cohort (p = 0.25). PH was associated with age > = 65, falls in the preceding year, diabetes, previous stroke, hypertension and Parkinson's disease. A simple score summing numbers of these variables performed equally well as weighted scores (AUROC 0.67 (0.59 to 0.74); p < 0.001). Rising DROP scores were incrementally predictive of future falls (χ2 for trend p < 0.01), increasing rates of decline in mini mental state examination (ANOVA p < 0.001) and mortality (HR 1.8 (1.6 to 2.0) per unit increment in DROP score; p < 0.001; figure). Figure. No caption available. Conclusions: The DROP score can predict presence of PH, future falls, and increased rates of mortality and cognitive decline. Application of the score could facilitate detection and management of PH. External validation of the DROP score is underway.